The Role of Materials in Achieving Sustainability for Existing BuildingsA Case Study of Educational Spaces in the Al-Jazeera Academy Building - Cairo - Dr. Haitham Emad El-Din Morsy; Dr. Ahmed Al Hussein Tohlob (Genius Journals, 2024)
The research addresses the impact of environmentally friendly buildings on human health. It notes that construction technology is evolving significantly in sustainable building materials. Studies indicate that Egypt is taking serious steps towards sustainability in the construction industry but lacks focus on the role of locally available sustainable materials. The problem highlights the inability of architectural structures to fulfill their role in preserving the environment and the health of users, as well as underutilization of many locally available sustainable materials. The study aims to understand the role of materials in achieving sustainable existing buildings and reducing energy consumption and environmental compatibility in Egypt. To achieve this goal, an analysis of the materials used in construction and their impact on the environment and human health is conducted. Factors influencing the choice of sustainable materials in Egypt, such as cost, availability, and environmental awareness, are also studied. The focus is also on policies and legislation related to sustainability in the construction industry in Egypt and their impact on the choice of sustainable materials. Suggestions are made to promote the use of sustainable materials and improve awareness of their importance among architects, contractors, and consumers.
Keywords: among; promote; legislation; materials